Inverse analysis of oxygen diffusivity in oak wood using the back-face method: application to cooperage - Roussey, Claire; Perré, Patrick; Casalinho, Joel; Colin, Julien (Wood science and technology, 2022)
During the aging of wines and spirits in oak barrels, oxygen diffusion through the wood occurs and leads to mild oxygenation of the beverage. In this study, the oxygen diffusivity in oak wood was determined by inverse analysis using the back-face method. In the measurement setup, a defined oxygen concentration was applied to the front of a sample and the variation of oxygen concentration due to gas diffusion through the sample was measured on the back. The experiment was carried out simultaneously on several samples. It was then possible to study 36 samples and to assess the effect of several parameters in a reasonable time. A finite volume model using the actual experimental conditions as boundary conditions was implemented for the identification of the diffusion coefficient. The obtained values range between 4.64 × 10 −11 and 2.02 × 10 −9 m 2 s −1 and highlight the high heterogeneity of oak wood. Such low values, compared to the diffusion of oxygen in air (a factor 10 5 lower), reflect the huge tortuosity of oak wood in its tangential direction.